Validitas Aspek Kebahasaan dan Keterbacaan dalam Pengembangan Bahan Ajar MKWU Bahasa Indonesia Berbasis Kearifan Lokal - Asep Hidayatullah; Mulyani, Sri; Munir, Sirojul (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2022)
This study aimed to describe the development of Indonesian language learning materials and determine the feasibility of learning materials' linguistic and legibility aspects. The R & D (Research and Development) method was used to achieve the research objectives. This research was started by assessing the potential and problems, collecting data, designing the product, validating, revising, and testing products. As a result, the learning materials developed in this study were in the form of printed teaching materials, namely brochures. The teaching materials consisted of four components: titles, basic competencies or subject matter, supporting information, and assessments. The development of learning materials focused on basic writing skills, namely the ability to use effective sentences, develop paragraph writing, academic writing, scientific articles, citing rules, and writing a bibliography. The assessment results show that the Indonesian language learning materials developed are in good category, with an average score of 3.75 and a feasibility level of 75% (adequate).